China's rise: Perceptions and misperceptions - Krishnan Srinivasan (European Centre for International Political Economy (ECIPE), 2013)
In a new paper - presented at an ECIPE Conference - Krishnan Srinivasan, former Foreign Secretary of India, analysed the political direction of China and its consequences for Europe and the world.
Keywords: 330